Human rights: has the present economic crisis proven Bentham was right? - Calheiros, Maria Clara (2015)
In recent years several southern European countries have become submerged by an economic crisis which has led to controversial legal changes. Moreover, in countries such as Portugal or Spain, people’s rights, once considered well established and undisputed, are now seen as something the State cannot afford to grant to its citizens. In this paper, the author reviews some of Jeremy Bentham’s philosophical arguments regarding the French declaration of rights as a starting point from which to examine the contemporary discourse that has been used to support those legal changes. At the end of the day, the main focus of this paper is to observe to what extent Bentham's criticisms on human rights remain relevant and are, in fact, being used.